2021
DOI: 10.3390/ijms22041869
|View full text |Cite
|
Sign up to set email alerts
|

Complexation with Random Methyl-β-Cyclodextrin and (2-Hidroxypropyl)-β-Cyclodextrin Enhances In Vivo Anti-Fibrotic and Anti-Inflammatory Effects of Chrysin via the Inhibition of NF-κB and TGF-β1/Smad Signaling Pathways and Modulation of Hepatic Pro/Anti-Fibrotic miRNA

Abstract: Chrysin (CHR) is a natural flavonoid with a wide range of pharmacological activities, including hepatoprotection, but poor water solubility. By including water-soluble hydroxypropyl (HPBCD) and randomly methylated (RAMEB) β-cyclodextrin, we aimed to increase its biodisponibility and the effectiveness of the antifibrotic effects of chrysin at oral administration. Liver fibrosis in mice was induced in 7 weeks by CCl4 i.p. administration, and afterwards treated with 50 mg/kg of CHR-HPBCD, CHR-RAMEB, and free chry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recognized for its various therapeutic properties, CHR exhibits antiinflammatory, anticancer, and antioxidant activities [7,8]. Recent studies have also highlighted its potential antifibrotic effects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recognized for its various therapeutic properties, CHR exhibits antiinflammatory, anticancer, and antioxidant activities [7,8]. Recent studies have also highlighted its potential antifibrotic effects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested a critical role of inhibitory Smad, Smad7 in the crosstalk between TGF-β and NF-κB signaling ( Chen et al, 2018b ). The upregulation of Smad7 and its interaction with NF-κB subunit p65 suppresses TGF-β-Smad signaling ( Ciceu et al, 2021 ). On the other hand, an increase in the expression of Smad7 can also induce IκBα, thereby inhibiting NF-κB activation ( Lu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect could be attributed to the suppression of NF- κ B. In many other studies, NF- κ B was a common pathway by which chrysin has been shown to exert its beneficial effects [ 52 , 64 , 65 , 71 ].…”
Section: Discussionmentioning
confidence: 99%